Factors associated with use of hormone therapy after preventive oophorectomy in BRCA mutation carriers. Issue 12 (December 2020) - Mejia-Gomez, Javier; Gronwald, Jacek; Senter, Leigha; Karlan, Beth Y.; Tung, Nadine; Wolfman, Wendy; Demsky, Rochelle; Sun, Ping; Narod, Steven A.; Kotsopoulos, Joanne
Abstract: Objective: Bilateral salpingo-oophorectomy (oophorectomy) is recommended to women with a germline BRCA1 or BRCA2 mutation before natural menopause to prevent ovarian and fallopian tube cancer. The adverse effects of early surgical menopause are well established. Although many of the side effects can be ameliorated by the use of hormone therapy (HT); use of HT in this group of predominantly young patients remains suboptimal. The goal of this study was to identify the frequency of HT use, as well as predictors of HT uptake in BRCA mutation carriers who underwent preventive oophorectomy before natural menopause. Methods: Eligible participants were identified from a longitudinal study of BRCA mutation carriers. We included premenopausal women with no personal history of cancer who underwent oophorectomy before age 50 and who had a minimum of 2 years of follow-up. Detailed information on HT use and other important variables was collected by a research questionnaire every 2 years. Descriptive statistics were used to evaluate the use of HT in various subgroups. Results: A total of 793 women with a BRCA1 or BRCA2 mutation were included in this analysis. The mean age at oophorectomy was 42 years (range 28-49). Sixty-one percent of the women reported using HT after oophorectomy. Factors associated with HT use included young age at surgery, a high level of education and preventive mastectomy. Conclusions: The uptake of HT after oophorectomy in women with a BRCA1 or BRCA2 mutation varies by age, education, and surgical history. Clinician and patient awareness may lead to better utilization of HT in women who undergo oophorectomy at an early age to help mitigate the adverse effects associated with surgical menopause.